Fluoride concentration of some brands of fermented milks available in the market - Lodi, Carolina Simonetti [UNESP]; Manareli, Michele Maurício [UNESP]; Sassaki, Kikue Takebayashi [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Martinhon, Cleide Cristina Rodrigues [UNESP] (My University, 2011)
Objectives: To evaluate the fluoride ion concentration in some fermented milks present in the market. Methods: Three brands of 6 fermented milks (Parmalat®-uva, Chamyto®, Paulista®, Batavito®, Yakult®, Vigor Club®) were analyzed. Fluoride concentration was evaluated after facilitated microdiffusion by HDMS. Results: Parmalat® products ranged from 0.022 μgF/g to 0.031 μgF/g, Chamyto® from 0.228 μgF/g to 0.272 μgF/g, Paulista® from 0.182 μgF/g to 0.220 μgF/g, Batavito® from 0.028 μgF/g to 0.030 μgF/g, Yakult® from 0.115 μgF/g to 0.206 μgF/g and Vigor Club® from 0.808 μgF/g to 1.171 μgF/g. Conclusions: The presence of fluoride could be observed in all of the fermented milks analyzed which can contribute with the total fluoride daily intake.
Keywords: Children; Dental fluorosis; Fluoride; Milk-fermentation